ANALISIS PENGENDALIAN KUALITAS PRODUK LEMARI PADA MEUBEL PADA PESONA JEPARA - Rueng, Margareta; Hattu, Lukas J.B.B; Giri, Erna E (LPPM Universitas Sains dan Teknologi Komputer, 2025)
This research aims to identifi and analyze the quality control of wardrobe products at Meubel Pesona Jepara in Penfui, Kupang City. This research is a case study which focuses on quality control carried out by the company to minimize defects in cabinet products in Pesona Jepara Furniture in Penfui, Kupang City. The date Collection techniques used in this research are observation, interviews, documentation and questionnaieres, while the analysis techinque used in this research is the Pareto diagram as atool to find the most dominant product at Pesona Jepara Furniture in Penfui, Kupang City. The results of this research show that quality control of cupboards in 2023 with 3 types of product defects, namely 9 cupboards not conforming to order specifications (39%), 8 Cupboards had rotten wood (35%), and 6 cupboards had broken wood (26%). From the analysis of the cause and effect diagram, it can be seen that the factors causing damage or damage in production orginate from human/ employee factors, work methods and materials/ raw materials.